Effect of Intravenous Infusion of Lidocaine Compared with Ultrasound-Guided Transverse Abdominal Plane Block on the Quality of Postoperative Recovery in Patients Undergoing Laparoscopic Bariatric Surgery - Sun J; Wang S; Wang J; Gao X; Wang G (Dove Medical Press, 2022)
Jing Sun,1,2 Shan Wang,1,2 Jun Wang,1,2 Xiuxiu Gao,1,2 Guanglei Wang1,2 1Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of China; 2Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of ChinaCorrespondence: Guanglei Wang, Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, No. 99 Huaihai West Road, Xuzhou, 221000, People's Republic of China, Tel +8613852087156, Email 13852087156@163.comPurpose: To investigate the effect of intravenous infusion of lidocaine compared with ultrasound-guided transverse abdominal plane (TAP) block on the quality of postoperative recovery and analgesic effect in patients undergoing bariatric surgery.Patients and Methods: Ninety-nine ASA II-III patients scheduled for elective laparoscopic bariatric surgery were randomized into the lidocaine group (group L), transverse abdominal plane block group (group T), and control group (group C). Group L: a loading dose of 1.5 mg/kg lidocaine was given at induction, followed by 2 mg·kg− 1·h− 1 maintenance until the end of surgery. Group T: ultrasound-guided bilateral administration of 0.25% ropivacaine in the transverse abdominal plane was given after induction of general anesthesia. Group C: no additional treatment was performed. Quality of recovery-40 (QoR-40) was assessed at 24 h after surgery. Consumption of propofol and remifentanil, visual analog scale (VAS) pain scores at rest at 0, 6, 12, and 24 h postoperatively, time to return of intestinal function, use of remedial analgesics within 24 h after surgery, adverse reactions were recorded.Results: Compared with Group C, Group L and Group T had higher QoR-40 scores at 24 h postoperatively, and the difference was statistically significant (P=0.002 and P=0.003, respectively). However, there was no difference between Group L and Group T (P=0.128). In addition, compared with those of Group T and Group C, VAS scores at 12 h and 24 h postoperatively were lower in Group L (P < 0.0166).Conclusion: Both intravenous infusion of lidocaine and ultrasound-guided TAP block provided good postoperative recovery and postoperative analgesia for patients with bariatric surgery, and intravenous infusion of lidocaine provided better analgesia at 12 h and 24 h postoperatively compared with TAP block.Keywords: lidocaine, TAP block, bariatric surgery, postoperative recovery, postoperative pain